STRATEGI PENYUSUNAN STANDAR PELAYANAN PUBLIK DENGAN PENDEKATAN PARTISIPASI MASYARAKAT DAN STAKEHOLDERS - Gedeona, Hendrikus Triwibawanto (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2011)
Citizens as the customers and owners of public services should be involved as the key actor in improving public service quality. Therefore, citizen participation should be placed as the leverage for the government to improve public service,including in the formulation of public service standard. Through participation, citizens are initially expected to recognize: first, the types and forms of services they need; second, the way of service delivery; third, the mechanism to proportionate the roles of stakeholders in formulation and delivery and to collectively commit to improve public service quality based on the existing public service standard. The shift of paradigm of citizens from 'being customers' to 'being owners' confers more strategic implications for local government. This is because local government is responsible for public service delivery in order that the citizens are able to pursue their daily activities.